2014
DOI: 10.9775/kvfd.2014.10678
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single or Combined Dietary Supplementation of Boric acid and Plant Extract Mixture on Egg Production, Egg Quality and Blood Cholesterolemia in Laying Hens

Abstract: SummaryThis experiment was conducted to determine the effects of boric acid (BA) (60 mg/kg of feed) and plant extract mixture (Fitococci, F) (0.75 g/kg of feed), individually or in combination, on egg production, egg quality parameters and blood cholesterol concentration of laying hens in 23 wk of age. After wk 7 of the trial the level of boric acid in feeds were increased to 180 mg/kg. The feeding period lasted 14 wk. One hundred ninety-two pullets (Hyline) were randomly divided into control and 3 treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
5
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 0 publications
5
5
4
Order By: Relevance
“…The present study showed that Cd had a significant impact on shape index (P < 0.01) however, the shape index had not affected by the boron supplementation compare with control (P > 0.05). Consistent with our results, a previous study showed that shape index was not affected by boric acid (60 and 180 mg/kg) supplementation to the diets [19].…”
Section: Resultssupporting
confidence: 93%
“…The present study showed that Cd had a significant impact on shape index (P < 0.01) however, the shape index had not affected by the boron supplementation compare with control (P > 0.05). Consistent with our results, a previous study showed that shape index was not affected by boric acid (60 and 180 mg/kg) supplementation to the diets [19].…”
Section: Resultssupporting
confidence: 93%
“…However, studies examining the effects of boron (Kaya and Macit, 2018) and vitamin D 3 (Yao et al, 2013) on fatty acids and cholesterol are very limited. It should be also stressed that although serum cholesterol level did not alter, yolk cholesterol concentration decreased in boric acid with vitamin D 3 supplementation group, which is consistent with the previous studies in which boron in combination with humate (Koksal et al, 2012) or plant extract mixture did not alter serum cholesterol concentration (Sizmaz et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…The previous studies showed that the body weight, feed intake, feed conversion ratio, egg production and egg weight were not affected by dietary boron in laying hens (Kurtoglu et al, 2002;Sizmaz et al, 2014), whereas the present results also showed that boric acid alone did not influence these parameters; however, when combined with a high dose of vitamin D 3 boric acid negatively increased feed efficiency. Koksal et al (2012) stated that 90 mg/kg dietary boric acid decreased the feed conversion ratio of laying hens in comparison to control in the 5-6 th weeks of the trial.…”
Section: Discussioncontrasting
confidence: 47%
“…While, Shape index, yolk color score, albumen % and yolk % were not affected by supplemented boron. Similar results were confirmed by Sizmaz et al (2014). Mineral contents of the eggshell Data of Figure 1 illustrate that there was a significant effect (p<0.01) of adding boron to layer diets at different levels on calcium, phosphorus and boron contents of the eggshell.…”
Section: Discussionsupporting
confidence: 79%
“…Results are in agreement with those reported by Mizrak et al (2010) who found that, supplementation of 25-200 mg boron/kg to hens during a period of 4-64 weeks of age did not affect the productive performance of the layers. Similarly, Sizmaz et al (2014) showed no significant effect in the egg production, feed intake and feed efficiency of laying hens fed diet added with 60 and 180 mg boric acid/kg. Olgun and Bahtiyarea (2015) indicated that, egg production, egg mass, feed intake and feed conversion ratio were not affected by dietary boron at 60 and 120 mg boron/kg in the laying hens.…”
Section: Discussionmentioning
confidence: 86%